Language and Writing Among the Kurds in the Middle Ages in the Historical Knowledge of Islamic Civilization - زينل, اراس فريق; عاریف, زريان سالار حمه (Sulaimani Journal for Humanities, 2020)
With no doubt Kurd is one of the region nations that has deep root in human history, They have their won language, which is a mirror of their culture, heritage and deep civilization. When we go back to the origin history books, archaeology evidences, cuneiform writings and even civil epics and oral history we come across the fact that Kurdish Language has a deep root in civilization and its an original language among other languages. In fact, Kurdish Language has not introduced to readers as same as other languages. therefore, more research like this is very crucial. The title of this article is (Kurdish Language in the Medieval Centuries - under the Light of Islamic Civilization. This article will prove the exit of Kurdish Language during the Medieval Centuries.